Imam Abu Jaafar At-Thabary: Mufassir’s Scholar - bin Adnan, Boihaqi (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2023)
Imam Abu Jaafar at-Thabari, may Allah have mercy on him, is the only well-known reference in the study of the interpretation of bil Ma'tsur because of his ability to interpret the Qur'an, guided mainly by the good narrations of the prophet Muhammad (peace be upon him), his sahaba (may Allah be pleased with him), the tabiin, and tabi' tabiin, so that the scholars from generations to generations have made Imam Abu Jaafar at-Thabari the supreme teacher of the Mufassir. This qualitative research seeks to better understand Imam Abu Jaafar at-Thabari's thoughts by conducting library research and collecting data from various literatures. The results of the study prove that Imam Abu Jaafar at-Thabari and his interpretation book, Jami` al-Bayan: Verses of Qur’an Interpretation, can be a major foothold in the development of Al-Qur'an interpretation throughout the world. In terms of method, he prioritizes the interpretation of bil ma'tsur because it is more postulated and precise in uncovering the secrets of the contents of the Qur'an. It is a guide to solving various problems for people.